Tingkat Perbedaan Serum Nitric Oxide terhadap Derajat Keparahan dan Durasi Psoriasis - Ambar Aliwardani; Bobby Febrianto; Fiska Rosita; Putti Fatiharani Dewi; Muhammad Eko Irawanto (MEDICINUS, 2022)
Psoriasis belongs to erythrosquamous dermatosis with uncertain etiology. Nitric oxide (NO) that acts as growth and differentiation regulator of keratinocytes is thought to play an important role in the pathogenesis of this disease. This study was aimed to determine the difference of nitric oxide serum level with the severity and duration of psoriasis patients. A cross-sectional study was conducted in 22 subjects with psoriasis vulgaris in the outpatient clinic of Dr. Moewardi Hospital Surakarta from May-September 2018 with 22 healthy individuals as control group. The severity of psoriasis was assessed using psoriasis area severity index (PASI), and serum NO is measured using Greiss method. Data then analysed using T-test and Kruskal Wallis tests (p<0.05). There was a significant difference in serum NO between the psoriasis patients and control group (p=0.020); there was no significant difference between serum NO patients and PASI score and duration of disease. It can be concluded that NO is an important factor in the inflammatory process in psoriasis, especially in active lesion.